Associations of blood glucose and prevalent diabetes with risk of cardiovascular disease in 500 000 adult Chinese: the China Kadoorie Biobank. - Bragg, F; Li, L; Smith, M; Guo, Y; Chen, Y; Millwood, I; Bian, Z; Walters, R; Chen, J; Yang, L; Collins, R; Peto, R; et al. (Blackwell Publishing Ltd, 2014)
AIMS: To examine the relationship of self-reported diabetes, and of random blood glucose levels among individuals without known diabetes, with the prevalence of cardiovascular disease in Chinese adults. METHODS: We examined cross-sectional data from the China Kadoorie Biobank of 0.5 million people aged 30-79 years recruited from 10 diverse regions of China in the period 2004-2008. Logistic regression was used to estimate the odds ratios of prevalent cardiovascular disease associated with self-reported diabetes, and with measured random blood glucose levels among participants with no history of diabetes, adjusting simultaneously for age, sex, area, education, smoking, alcohol, blood pressure and physical activity. RESULTS: A total of 3.2% of participants had self-reported diabetes (men 2.9%; women 3.3%) and 2.8% had screen-detected diabetes (men 2.6%; women 2.8%), i.e. they had no self-reported history of diabetes but a blood glucose level suggestive of a diagnosis of diabetes. Compared with individuals without a history of diabetes, the odds ratios associated with self-reported diabetes were 2.18 (95% CI 2.06-2.30) and 1.88 (95% CI 1.75-2.01) for prevalent ischaemic heart disease and stroke/transient ischaemic attack, respectively. Among participants without self-reported diabetes there was a positive association between random blood glucose and ischaemic heart disease and stroke/transient ischaemic attack prevalence (P for trend <0.0001). Below the diabetic threshold (<11.1 mmol/l) each additional 1 mmol/l of random blood glucose was associated with 4% (95% CI 2-5%) and 5% (95% CI 3-7%) higher odds of prevalent ischaemic heart disease and stroke/transient ischaemic attack, respectively. CONCLUSIONS: In this adult Chinese population, self-reported diabetes was associated with a doubling of the odds of prevalent cardiovascular disease. Below the threshold for diabetes there was still a modest, positive association between random blood glucose and prevalent cardiovascular disease.